2014
DOI: 10.1111/ele.12355
|View full text |Cite
|
Sign up to set email alerts
|

Hybridisation is associated with increased fecundity and size in invasive taxa: meta‐analytic support for the hybridisation‐invasion hypothesis

Abstract: The hypothesis that interspecific hybridisation promotes invasiveness has received much recent attention, but tests of the hypothesis can suffer from important limitations. Here, we provide the first systematic review of studies experimentally testing the hybridisation-invasion (H-I) hypothesis in plants, animals and fungi. We identified 72 hybrid systems for which hybridisation has been putatively associated with invasiveness, weediness or range expansion. Within this group, 15 systems (comprising 34 studies)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 105 publications
(193 reference statements)
8
139
0
Order By: Relevance
“…). These results are consistent with the hypothesis that crop–wild hybrid biotypes have the potential to displace their wild parent in certain environments (Ellstrand and Schierenbeck ; Hovick and Whitney ).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…). These results are consistent with the hypothesis that crop–wild hybrid biotypes have the potential to displace their wild parent in certain environments (Ellstrand and Schierenbeck ; Hovick and Whitney ).…”
Section: Methodssupporting
confidence: 89%
“…; Hendry ; Whitney et al. ) and thus contribute to weedy population growth (Hovick and Whitney ). Therefore, gene flow between genetically distinct crops and sexually compatible weedy relatives may contribute to the evolution of more problematic weeds when gene flow alters phenotypic frequencies and the relative fitness of phenotypes within weed populations.…”
Section: Introductionmentioning
confidence: 99%
“…Elaborating on this hypothesis, Mark Kirkpatrick provided evidence for a new example in which massive range expansion in the mosquito (and malaria vector) Anopheles gambiae may have been triggered by capture of a cassette of adaptive alleles from the dry-climate adapted A. arabensis. Mixing of genetic material from divergent (but not too divergent) populations within a species can also improve performance, as was shown by Katrina Dlugosch (University of Arizona, These patterns match recent trends in the literature: both intraspecific and interspecific admixture are commonly associated with performance increases in invasive plants, animals, and fungi (see syntheses in Rius & Darling, 2014;Hovick & Whitney, 2014). However, a fundamental question is still up for grabs: how critical is such admixture for invasive success?…”
supporting
confidence: 65%
“…With time, many cultivars escaped cultivation, spread beyond the ornamental confines of the garden and became weeds (Spies 1984, Swarbrick 1985, Palmer and Pullen 1995. Studies have identified hybridization to contribute substantially to invasiveness, weediness and/or range expansion (Brown and Marshall 1981, Ellstrand and Schierenbeck 2000, Hovick and Whitney 2014. Likewise, innumerable intentional as well as unintentional hybridization events in Lantana led to remarkable increase in its complexity.…”
Section: Historical Events Leading To the Species Complexmentioning
confidence: 99%